Extraction and Purification of Lipases Enzyme from Germinating Seeds of Four Crops - Al-Haidari, Alaa M. Dh.; Khudhair, Saad H.; Alsaadawi, Ibrahim S. (Iraqi Journal of Science, 2020)
Lipase enzyme has attracted a lot of attention in recent years because of its diverse biotechnological applications. The present study was conducted to screen germinated seeds of four crops, namely sunflower (Helianthus annuus), flaxor linseed (Linum usitatissimum ), peanut (Arachis hypogaea ) and castor bean (Ricinus communis), for the activity of their lipases. to the study also included the extraction and purification of lipase from the seeds of the most promising crop using different solvents.The results indicated that the maximum enzymatic activity (0.669 U/ml) was obtained when 0.1 M Tris-HCl buffer extract was used after 3 days of seed germination of all the tested species, as compared to the other test solvents (acetone and water). Sunflower germinated seeds showed the highest lipase activity, which was higher by 159.67, 185.32, and 285.90 % over the activities of castor bean, flax, and peanut seeds, respectively. Among the used ranges of saturation of ammonium sulfate, the ratio of 70% was the best in precipitating the crude enzyme, showing a highest specific activity of 2.576 U/ mg protein.The first stage of gel filtration chromatography column by Sephadex G-200 indicated the presence of two non-identical peaks, one for protein and another for lipase activity, between the fractions of 18 to 23. The active fractions were pooled and loaded again in the Sephadex G-200 column and the eluted fractions showed two identical peaks, one for protein and another for lipase activity, between the fractions of 19 to 23. The final purification step by gel filtration showed a specific activity of 6.482 U/mg proteins with a yield of 38.75 % and 11.33 folds of time of purification. The study revealed that sunflower seeds are a better source of lipase as compared to the other used plant seeds, which can be used in different industries.